Frank [videorecording (DVD)] - Fassbender, Michael, 1977-; Gleeson, Domhnall, 1983-; Gyllenhaal, Maggie, 1977-; McNairy, Scoot (Magnolia Home Entertainment, 2014)
An offbeat comedy about a young wannabe musician, Jon, who finds himself out of his depth when he joins an avant-garde pop band led by the mysterious and enigmatic Frank, a musical genius who hides himself inside a large fake head, and his terrifying band mate Clara.